2005 Annual Conference Proceedings
DOI: 10.18260/1-2--15280
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Success In Learning Communities

Abstract: In 1998, our department turned to the pedagogical innovation termed "learning communities" in an effort to enhance student retention and to bring coherence and meaning to our first-year student curriculum. We have found that our learning community has provided an opportunity for agricultural engineering students to become involved in the Agricultural and Biosystems Engineering (ABE) department from the moment they arrive on campus. Not only has the learning community helped us to increase our first-year, first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…Similar results were also seen in the School of Engineering and Computer Science in West Texas A&M University, Indiana University Purdue University Indianapolis (IUPUI) and Virginia Tech University [2] - [4]. Introduction of learning communities in agriculture engineering and technology programs in Iowa State University improved the retention rate by 12.3% in a year [5]. Additionally, some studies have linked learning communities with enhanced academic performance and communication skills in the students [5].…”
Section: Background and Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…Similar results were also seen in the School of Engineering and Computer Science in West Texas A&M University, Indiana University Purdue University Indianapolis (IUPUI) and Virginia Tech University [2] - [4]. Introduction of learning communities in agriculture engineering and technology programs in Iowa State University improved the retention rate by 12.3% in a year [5]. Additionally, some studies have linked learning communities with enhanced academic performance and communication skills in the students [5].…”
Section: Background and Introductionsupporting
confidence: 59%
“…Introduction of learning communities in agriculture engineering and technology programs in Iowa State University improved the retention rate by 12.3% in a year [5]. Additionally, some studies have linked learning communities with enhanced academic performance and communication skills in the students [5]. A study conducted by Mickelson and Brumm (2005) found that learning communities enhance the sense of community in the students and alleviate the student-faculty relationship.…”
Section: Background and Introductionmentioning
confidence: 99%
See 1 more Smart Citation